Las comisiones de esclarecimiento y la consolidación del campo de la historia del tiempo presente en Colombia y México - Fernanda Espinosa Moreno (Caravelle)
This article deals with relations between history of the present’s field and transitional mechanisms that produced narrations about recent past in periods of violence. Four commisions in Mexico and Colombia that, even if they shared the study’s object, presented different characteristics. In order to do this, we’ve compared the commisions’ composition, their archives, the periods included in the studies and the methods employed, and their influence in the development of history of the present.